Epidemiology, Diagnosis, and Treatment of Atopic Dermatitis in the Developing Countries of Asia, Africa, Latin America, and the Middle East: A Review - Yuri I. Lopez Carrera; Anwar Al Hammadi; Yu-Huei Huang; Lyndon J. Llamado; Ehab Mahgoub; Anna M. Tallman (Adis, Springer Healthcare, 2019)
Abstract Atopic dermatitis (AD), the leading cause of skin-related burden of disease worldwide, is increasing in prevalence in developing countries of Asia, Africa, Latin America, and the Middle East. Although AD presents similarly across racial and ethnic groups as chronic and relapsing pruritic eczematous lesions, some features of the disease may be more or less prominent in patients with darker skin. Despite a similar presentation, consistent diagnostic criteria and consistent treatment guidelines are lacking. Because of these and other challenges, adherence to treatment guidelines is difficult or impossible. Previous studies have stated that many patients with AD receive ineffective or inappropriate care, such as oral antihistamines, oral corticosteroids, or traditional medicines, if they are treated at all; one study showed that approximately one-third of patients received medical care for their dermatologic condition; of those, almost three-quarters received inappropriate or ineffective treatment. In addition, other challenges endemic to developing countries include cost, access to care, and lack of specialists in AD. Furthermore, most of the available diagnostic criteria and treatment guidelines are based on European and North American populations and few clinical trials report the racial or ethnic makeup of the study population. Drug pharmacokinetics in varying ethnicities and adverse effects in different skin physiologies are areas yet to be explored. The objective of this review is to describe the diagnosis, treatment, and management of AD in developing countries in Asia, Africa, Latin America, and the Middle East; to discuss the differences among the countries; and to establish the unmet needs of patients with AD in them. The unmet medical need for treatment of AD in developing countries can be addressed by continuing to train medical specialists, improve access to and affordability of care, and develop new and effective treatments. Funding Pfizer Inc.